Design and Validation of a Reverse Phase HPLC Method for Simultaneous Determination of Doxycycline and Metronidazole in Targeted Periodontal Therapy - Anuj Kumar; Phool Chandra; Anurag Verma; Vishal Trivedi; Amit Sharma; Himanshu Sharma; Arvind Raghav; Neetu Sachan (Oriental Journal Of Chemistry, 2026)
The reverse-phase high-performance liquid chromatography (RP-HPLC) method has been shown to exhibit excellent repeatability, accuracy, and reproducibility when used to simultaneously assess doxycycline and metronidazole for the management of localised periodontal diseases.Low levels of interference were achieved through optimisation and high-resolution separation. Validation was accomplished according to recommendations from the International Conference on Harmonisation (ICH) and included assessments for linearity, accuracy, precision, limits of detection (LOD) and quantitation (LOQ), and robustness. The validation data demonstrated greater than 90% recovery and low %RSD, along with very high linearity (r² > 0.999) for both compounds over the entire concentration range, thereby confirming the reliability of the method.The presented approach is suitable for routine quality control analysis of mixed doxycycline and metronidazole dose forms.